RANCANG BANGUN SISTEM MONITORING KONDISI AKI PADA KENDARAAN BERMOTOR - Leonandi Agustian . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2015)
Abstract–A motor cycle requires a battery to store electrical energy in chemical formenergy, which will be used to supply power to the ignition system, lights and other electrical components.The problem that arises is motorcycle   users do not know the condition of the battery has reached the level of voltage is below average, for example for dry battery voltage level is the lowest Advice on to 10,5 voltswith battery temperature up to 30 degrees Celsius. Another thing to consider is that the component ofregulator and the dynamo charge where the value of the voltage generated by the dynamo charge a  good and  normal is  the  range of  13,4  V- 14,8V.Do  a  design  of  electronic  devices  that  can monitor  the  condition  of  the  battery  temperature, battery voltage, battery current, motor cycle  imformasi is processed by microcontroller ATMega16 and displayed on a 16 X 4 LCD screen that can be placed at the front of the vehicle. So users will be able to know the  condition of  the  vehicle  battery  directly  without having hassles disassemble the battery to see the condition of electricity in a motor cycle.   Keywords:Voltage Sensor, Current Sensor ACS712,Temperature Sensor DHT11, Microcontroller ATMega16, LCD 16 X 4